Engineered nanoparticle exposure and cardiovascular effects: the role of a neuronal-regulated pathway. (24th August 2018) - Kan, H.; Pan, D.; Castranova, V.
Abstract: Human and animal studies have confirmed that inhalation of particles from ambient air or occupational settings not only causes pathophysiological changes in the respiratory system, but causes cardiovascular effects as well. At an equal mass lung burden, nanoparticles are more potent in causing systemic microvascular dysfunction than fine particles of similar composition. Thus, accumulated evidence from animal studies has led to heightened concerns about the potential short- and long-term deleterious effects of inhalation of engineered nanoparticles on the cardiovascular system. This review highlights the new observations from animal studies, which document the adverse effects of pulmonary exposure to engineered nanoparticles on the cardiovascular system and elucidate the potential mechanisms involved in regulation of cardiovascular function, in particular, how the neuronal system plays a role and reacts to pulmonary nanoparticle exposure based on both in vivo and in vitro studies. In addition, this review also discusses the possible influence of altered autonomic nervous activity on preexisting cardiovascular conditions. Whether engineered nanoparticle exposure serves as a risk factor in the development of cardiovascular diseases warrants further investigation.